The universe of things : on speculative realism - Shaviro, Steven (Posthumanities ;, 2014)
"From the rediscovery of Alfred North Whitehead's work to the rise of new materialist thought, including object-oriented ontology, there has been a rapid turn toward speculation in philosophy as a way of moving beyond solely human perceptions of nature and existence. Now Steven Shaviro maps this quickly emerging speculative realism, which is already dramatically influencing how we interpret reality and our place in a universe in which humans are not the measure of all things. The Universe of Things explores the common insistence of speculative realism on a noncorrelationist thought: that things or objects exist apart from how our own human minds relate to and comprehend them." "Bringing together a wide array of contemporary thought, The Universe of Things is an invaluable guide to the evolution of speculative realism and the provocation of Alfred North Whitehead's pathbreaking work."--Publisher's description